Management of Rhinophyma on the basis of different excision procedures - Biswari, Gaurav; Gupta, Pragati; Das, Dilip (Journal of College of Medical Sciences-Nepal, 2010)
The aim is to get better cosmetic results after the excision of rhinophyma because there are various procedures to excise rhinophyma in which Electrocautery is the most convenient and can be performed under local anaesthesia also. Key words: Rhinophyma; electrocautery; anaesthesia DOI: 10.3126/jcmsn.v6i2.3618 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 50-55